2019
DOI: 10.5152/tud.2018.96393
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation index and human papilloma virus in males with previous assisted reproductive technology failures

Abstract: In cases with previous ICSI failures, the prevalence of HPV infection in semen is not higher than previously reported infertile populations. The reproductive outcome might be impaired in HPV-positive semen due to lower number of good quality embryos, which needs to be clarified by further large population-based studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
8
0
6
Order By: Relevance
“…Recent studies have shown that infection by different microorganisms can result in increased DFI (Tangal et al, 2018;Zeyad et al, 2018). A study by Boeri et al investigated the potential impact of human papillomavirus (HPV) on sperm DNA integrity in subfertile men.…”
Section: Sperm Dfi As a Promising Determiner Of Male Infertilitymentioning
confidence: 99%
“…Recent studies have shown that infection by different microorganisms can result in increased DFI (Tangal et al, 2018;Zeyad et al, 2018). A study by Boeri et al investigated the potential impact of human papillomavirus (HPV) on sperm DNA integrity in subfertile men.…”
Section: Sperm Dfi As a Promising Determiner Of Male Infertilitymentioning
confidence: 99%
“…Nitekim bazı çalışmalarda IVF uygulanan ve düşükle sonuçlanan gebeliklerde HPV prevalansının yüksek olduğu ancak HPV pozitifliğinin gebe kalma oranlarını değiştirmediği bildirilmiştir [18] . Ülkemizde mikroenjeksiyon başarısızlığına HPV'nin etkisinin araştırıldığı bir çalışmada; semen örneklerinde %7.7 oranında pozitiflik saptanmış fakat çalışmamızda olduğu gibi gebelik başarı oranlarında anlamlı bir fark yaratmadığı görülmüştür [19] . Perino ve arkadaşları erkeklerde %9.5 ve kadınlarda %17.5 HPV pozitifliği saptadıkları çalışmalarında; özellikle erkek HPV infeksiyonlu çiftlerin gebelik kayıplarında HPV negatiflere kıyasla ciddi artış olduğunu (%66.7-15) belirtmişler fakat HPV pozitif çiftlerin gebelik başarısının değişmediğini bildirmişlerdir [20] .…”
Section: Discussionunclassified
“…обнаружили, что при оплодотворении ВПЧ-положительной спермой получено значительно меньшее количество эмбрионов, имеющих хорошее качество на день переноса. Ранние спонтанные аборты в парах с инфицированным ВПЧ мужчиной произошли в 33 % случаев (в неинфицированных парах -в 10 %) [60].…”
Section: вирус папилломы человекаunclassified
“…Большинство проанализированных данных свидетельствует о том, что инфицирование сперматозоидов ВПЧ может быть причиной снижения фертильности посредством различных механизмов, действующих на разных этапах развития эмбриона [62], хотя имеются и противоположные данные: S. Tangal и соавт. не обнаружили различий в частоте имплантации яйцеклетки, наступления беременности и раннего выкидыша у пар, подвергшихся воздействию ВПЧ, и неинфицированных пар [60]. Дальнейшие исследования необходимы для лучшего понимания влияния ВПЧинфекции на частоту раннего невынашивания беременности и других неблагоприятных исходов беременности.…”
Section: вирус папилломы человекаunclassified